Neanderthal diet at Vindija and Neanderthal predation : the evidence from stable isotopes - Richards, Michael P. (Array, 2000)
Archeological analysis of faunal remains and of lithic and bone tools has suggested that hunting of medium to large mammals was a major element of Neanderthal subsistence. Plant foods are almost invisible in the archeological record, and it is impossible to estimate accurately their dietary importance. However, stable isotope ( d 13 C and d 15 N) analysis of mammal bone collagen provides a direct measure of diet and has been applied to two Neanderthals and various faunal species from Vindija Cave, Croatia. The isotope evidence overwhelmingly points to the Neanderthals behaving as top-level carnivores, obtaining almost all of their dietary protein from animal sources. Earlier Neanderthals in France and Belgium have yielded similar results, and a pattern of European Neander-thal adaptation as carnivores is emerging. These data reinforce current taphonomic assessments of associated faunal elements and make it unlikely that the Neanderthals were acquiring animal protein principally through scavenging. Instead, these findings portray them as effective predators.